2006
DOI: 10.1084/jem.20060925
|View full text |Cite
|
Sign up to set email alerts
|

Intraluminal crawling of neutrophils to emigration sites: a molecularly distinct process from adhesion in the recruitment cascade

Abstract: The prevailing view is that the β2-integrins Mac-1 (αMβ2, CD11b/CD18) and LFA-1 (αLβ2, CD11a/CD18) serve similar biological functions, namely adhesion, in the leukocyte recruitment cascade. Using real-time and time-lapse intravital video-microscopy and confocal microscopy within inflamed microvessels, we systematically evaluated the function of Mac-1 and LFA-1 in the recruitment paradigm. The chemokine macrophage inflammatory protein-2 induced equivalent amounts of adhesion in wild-type and Mac-1−/− mice but v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
486
1
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 605 publications
(514 citation statements)
references
References 25 publications
22
486
1
5
Order By: Relevance
“…9 F). Finally, we confirmed that transmigration is CD11b-dependent because CD11b / neutrophils exhibited defective transmigration (unpublished data; Phillipson et al, 2006;Zhang et al, 2006). Adoptive transfer of neutrophils further supported impaired CD11b / neutrophil emigration into lungs (Fig.…”
Section: Rap1b Regulates Akt Activity Via the Phosphatase Shp-1supporting
confidence: 64%
See 2 more Smart Citations
“…9 F). Finally, we confirmed that transmigration is CD11b-dependent because CD11b / neutrophils exhibited defective transmigration (unpublished data; Phillipson et al, 2006;Zhang et al, 2006). Adoptive transfer of neutrophils further supported impaired CD11b / neutrophil emigration into lungs (Fig.…”
Section: Rap1b Regulates Akt Activity Via the Phosphatase Shp-1supporting
confidence: 64%
“…The neutrophil crawling and TEM steps are highly M 2 -integrin-dependent (Phillipson et al, 2006). Because Rap1b controls some adhesion-dependent cellular functions, including superoxide production (Fig.…”
Section: Rap1b Inhibits Akt Activation Via Cd11b Outside-in Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…After the capture of leukocytes on blood vessel walls, they polarize and migrate on the endothelial cells (ECs) lining the vessels, which is thought to enable them to find optimal sites for transendothelial migration (TEM; Schenkel et al, 2004;Phillipson et al, 2006). Leukocytes transmigrate either at EC junctions (paracellular TEM) or through individual EC (transcellular TEM; Carman and Springer, 2004;Millán et al, 2006;Vestweber, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…1) generated between the cell frontal and rear adhesion surfaces and the underneath substrate. As in previous works (Phillipson et al 2006;Sakamoto et al 2011;Allena and Aubry 2012;Allena 2013), such forces are assumed to be viscous and may be distinguished into a frontal (f adh, f ) and a rear (f adh,r ) force as follows…”
Section: Intra-synchronizationmentioning
confidence: 99%